ChemInform Abstract: Palladium‐Catalyzed Borylation of M‐Dibromobenzene Derivative and Its Applications in One‐Pot Tandem Suzuki—Miyaura Arenes Synthesis. Issue 11 (February 2016) - Xie, Dahai; Li, Rong; Zhang, Dengqing; Hu, Jiena; Xiao, Duoduo; Li, Xianying; Xiang, Yunjie; Jin, Wusong
Abstract: The title reaction delivers moderate yields of monomeric coupling products in addition to low amounts of dimeric, trimeric, and tetrameric products.